Monetary policy across inflation regimes - Valeria Gargiulo; Christian Matthes; Katerina Petrova (Federal Reserve Bank of New York, 2024)
Does the effect of monetary policy depend on the prevailing level of inflation? In order to answer this question, we construct a parsimonious nonlinear time series model that allows for inflation regimes. We find that the effects of monetary policy are markedly different when year-over-year inflation exceeds 5.5 percent. Below this threshold, changes in monetary policy have a short-lived effect on prices, but no effect on the unemployment rate, giving a potential explanation for the recent "soft landing" in the United States. Above this threshold, the effects of monetary policy surprises on both inflation and unemployment can be larger and longer lasting.
Keywords: C11; C12; C22; 330; monetary policy shocks; inflation; regime-dependence; outliers; nonlinear time series models